EKSTRAK ANTIOKSIDAN FENOLIK KULIT NANAS (Ananas comosus (L) Merr.) SEBAGAI PENGAWET ALAMI UNTUK MENGHAMBAT BAKTERI SELAMA PENYIMPANAN FILLET IKAN - deviantika, deviantika; Kusuma Dewi, Yohana Sutiknyawati; Hartanti, Lucky (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACT            Phenolic antioxidant extract of pineapple peel as preservative to inhibit bacteria growth during storage of fish fillets has been studied. This study aims to determine the phenolic content, antioxidant activity of the pineapple peel extract and to identify its potency as preservative in inhibiting bacteria during storage period of fish fillets. The study was carried out by maceration of the pineapple peel using methanol:aquades (70:30 v/v) to produce phenolic extract. It can be shown from the result that pineapple peel contained phenolic compound at 4,74 mgGAE/g, antioxidant activity at 33,24%. The extract of phenolic antioxidant of pineapple peel had a potency in inhibiting bacteria growth in fillet of nile tillapia. This ability was bacteriostatic as it can be seen from the total of bacteria in fish fillet which treated by lower exctract compare to control through bacteriostatic mechanism. Keywords: bacteriostatic, extraction, yield, pineapple varieties.